Assessing the Political Economy of Policy Instability and its Effect on Nigerian Economic Growth, 1970-2015 - Nwadike, Gerald Chimezie; Ani, Kelechi Johnmary; Ojakorotu, Victor (Journal of Reviews on Global Economics, 2019)
This study examines the political economy of policy instability and its effect on the Nigerian economic growth from 1970 to 2015. The study tries to measure the effect of political policy instability on the Nigerian economic growth, focusing on the assessment of the relationship between political instability and unsustainable national economic growth in Nigeria. The researchers adopts the two stage least square of the static model and ADF and PP unit root test structural co-integration test as well as Pariwise Granger Causality. The research findings revealed that there is significant effect of policy instability on the Nigerian economic growth during the chosen period of observation and that there is no causality relationship between political instability and unsustainable national economic growth in Nigeria during the chosen period of study. In the light of the research findings, the researchers recommend transformational leadership and constitutional reform in Nigeria, which will go a long way to calm down the effect policy instability on Nigerian economic growth and development. Again the study calls for the promotion of citizenship over indignity in order to achieve cooperation and participation of all the masses and communities in the development process.